Prediksi Usia Kelelahan Pegas Ulir dan Lower Suspension Arm Berdasarkan Pendekatan Strain Life Berdasarkan Bentuk Permukaan Jalan - Ajinar; Azhari (Yayasan Kawanad, 2022)
This study aims to determine the effect of road surface contours on fatigue life of coil springs and lower suspension arm. In this study, strain gauge was affixed to the critical point of the minibus front suspension coil springs based on stress distribution. Strain signal obtained was analyzed using the Coffin-Manson, Morrow, and SWT approaches. From the results of the chemical composition test, it was found that the coil springs were made of SAE 5160 and lower suspension arm made of AISI 1513. From the results of this study it can be concluded that when the vehicle drive on the damaged road, coil spring and lower suspension arm received greater stress so that provide shorter fatigue life. Fatigue life of coil spring on rough roads is 16% lower than city roads and 7% lower than flat roads. Whereas fatigue life of lower suspension arm on rough roads is 27% lower than city roads and 0.03% lower than flat roads. So that the coil spring components fail faster than the lower suspension arm. This is because the contour of the road surface provides a vertical load so that it is in accordance with the function of the coil spring which works to reduce the load vertically while the lower suspension arm function holds the load when turning.